Features of transferring the angular errors of the gear hobbing machine`s table drive to the tooth profile of the machined wheel - V.V. Bushuev; V.A. Eremyants; V.V. Molodtsov; V.A. Novikov (Известия высших учебных заведений. Поволжский регион:Технические науки, 2024)
Background. Modern gear hobbing machines design is based on mechatronic drives, which prompts questions about the influence of errors that occur in the main motion direct drives structure on the process of involute tooth profile forming. Materials and methods. Theoretical research has considered a methodology for constructing a mathematical model that describes the transfer of angular errors that occur during the operation of the vertical hobbing machine’s workpiece drive to the involute tooth profile. Results. The occurrence of notches on the involute tooth profile, perceived as roughness, is associated not only with the intermittent nature of the hobbing process but also with angular oscillations inevitably accompanying the operation of the vertical hobbing machine’s workpiece drive. The magnitude of the profile error resulting from angular position errors is determined by the amplitudes and frequencies of the sinusoidal components of the angular oscillations. Conclusions. A mathematical model has been developed that describes the mechanism of forming the tooth profile of a spur gear, taking into account only the influence of angular errors in the table drive, without considering other errors that inevitably occur during the gear machining process. The contribution of this error to the overall process of forming the tooth profile during machining on a machine tool requires further study.